2009
DOI: 10.4049/jimmunol.0802806
|View full text |Cite
|
Sign up to set email alerts
|

NKp44 Receptor Mediates Interaction of the Envelope Glycoproteins from the West Nile and Dengue Viruses with NK Cells

Abstract: Dengue virus (DV) and West Nile virus (WNV) have become a global concern due to their widespread distribution and their ability to cause a variety of human diseases. Antiviral immune defenses involve NK cells. In the present study, we investigated the interaction between NK cells and these two flaviviruses. We show that the NK-activating receptor NKp44 is involved in virally mediated NK activation through direct interaction with the flavivirus envelope protein. Recombinant NKp44 directly binds to purified DV a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
102
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 132 publications
(104 citation statements)
references
References 50 publications
1
102
0
1
Order By: Relevance
“…27 This may be due to the NCR receptor binding affinity for viral glycoproteins. 31 In addition, perforin expression was increased following exposure to KMLC. Resveratrol also upregulates perforin protein in NK cells and activates the MAPK pathway by NKG2D activation.…”
Section: Discussionmentioning
confidence: 98%
“…27 This may be due to the NCR receptor binding affinity for viral glycoproteins. 31 In addition, perforin expression was increased following exposure to KMLC. Resveratrol also upregulates perforin protein in NK cells and activates the MAPK pathway by NKG2D activation.…”
Section: Discussionmentioning
confidence: 98%
“…NKp30 or NKp46) [38]. Finally, it has been demonstrated that NKp44 interacts with envelope glycoproteins from the West Nile and dengue flaviviruses [31].…”
Section: Discussionmentioning
confidence: 99%
“…Over the last years, it has become increasingly evident that NK cells can use a third recognition strategy, which relies on direct recognition of pathogens by NK cell receptors with consequent activation of NK cell effector functions [7]. The possible receptors able to directly recognize whole micro-organisms or micro-organism-derived products include several members of the TLR family [13,28], intracellular receptors like NOD2 [29] or members of the NCR family [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…NKp30 recognizes the cellular ligands B7-H6, BAT3 (9,10), the HCMV protein pp65 (11), and heparan sulfate (HS) as a co-ligand (12). In contrast, however, the cellular ligands for both NKp44 and NKp46 are largely unknown, and the ligands identified to date for these two proteins are various virus hemagglutinins (13,14), flavivirus E-protein for NKp44 (15) and HS as a co-ligand (12,(16)(17)(18). Vimentin was reported as cellular ligand for NKp46 (19).…”
mentioning
confidence: 99%